Can environmental determinants explain Nontuberculous Mycobacteria geographic incidence? - Rocha, D (2020)
Introduction and Objectives: Nontuberculous mycobacteria (NTM) are opportunistic agents that have gained importance during the last decades due to their increasing incidence in high-risk populations. Their modes of transmission differ from person-toperson contact commonly described in Mycobacterium tuberculosis (MTB). In fact, NTM are frequently found in soil, natural waters and drinking-water distributions systems, emphasizing the contribution of environmental factors when discussing this disease’s susceptibility. Our aim is to evaluate the incidence of NTM in Portugal and to identify the main environmental variables related to it. Material and Methods: We performed a cross-sectional study centred on 2011 (date of the latest Portuguese census) from collected personal features and environmental data available in public databases. Environmental values when only known at the district level were interpolated using inverse distance weighting. A semiparametric poisson model was used to estimate NTM incidence. The non-parametric part of the model was obtained by using thin plate smoothing splines defined on the spatial component of the data. Results: 359 new NTM cases were notified during a five-year period. None of the environmental determinants studied was strong enough to predict NTM geographical incidence in Portugal (p > 0.05), except for population density (p < 0.001). Personal characteristics such as female sex (p < 0.001), age (p < 0.001) and Human Immunodeficiency Virus infection and Acquired Immune Deficiency Syndrome (HIV/AIDS) incidence (p < 0.001) are associated with an increase of NTM disease incidence. Conclusions: NTM appears to be more common in elderly women, especially if they have HIV/AIDS disease or if they live in urban, highly populated areas. Overall, female sex seems to assume the most relevant role when discussing predisposition to NTM disease. However, further studies are needed to evaluate the impact on NTM geographical incidence by other environmental and personal variables not included in this one.